Креативні технології адаптації персоналу в умовах форс-мажору - Сибірцев, В. В.; Сочинська-Сибірцева, І. М.; Sybirtsev, V.; Sochynska-Sybirtseva, I. (ЦНТУ, 2022)
Висунуто гіпотезу, що креативність технологій повинна визначатись їх неординарним характером і можливістю гнучкого пристосування до умов, які диктуються нестандартними, особливо екстремальними (надзвичайними) кризовими ситуаціями. З цією метою досліджена практика успішних компаній в контексті використання технологій адаптації персоналу. Наукова цінність дослідження полягає у визначе нні основних складових креативних технологій адаптації персоналу, які є начасними для вітчизняних організацій в умовах форс-мажорних обставин, а саме: психологічної, корпоративної, мотиваційної адаптації, убезпечення життя. A hypothesis has been put forward that the creativity of technologies should be determined by their extraordinary nature and the possibility of flexible adaptation to conditions that are dictated by non-standard, especially extreme (emergency) crisis situations. For this purpose, the practice of successful companies in the context of the use of personnel adaptation technologies has been researched. The authors focus on the urgent problem of determining priority areas for personnel adaptation in conditions of force majeure, developing methods and tools for retaining personnel, as well as implementing creative shifts within the framework of traditional personnel adaptation technologies. The scientific value of the investigation consists in determining the main components of creative technologies for adapting personnel, which are relevant for domestic organizations in conditions of force majeure, namely: psychological, corporate, motivational adaptation, life safety. It is concluded that the creativity of personnel adaptation technologies in force majeure depends on the professionalism of HR managers. The transformation of personnel adaptation technologies requires updating and expanding the competence of HR managers, taking into account dynamic changes in the processes taking place in the business environment in force majeure circumstances.
Creative Technologies for Personnel Adaptation in Conditions of Force Majeure
Keywords: адаптація персоналу; форс-мажор; креативні технології; HR-менеджмент; корпоративний комплаєнс; фасилітатор; емпатія; personnel adaptation; force majeure; creative technologies; HR management; corporate compliance; facilitator; empathy; well-being; Employee Value Proposition; Diversity&Inclusion